PERAN SOSIAL MEDIA DALAM MENINGKATKAN KINERJA PEMERINTAH - Rakhmat Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
This purpose of this research is to know how to use the social media non-government that is to become one of the benchmarks for government performance. Based on instagram account @palembng.update, as social media that has 308K followers, it is often the place for complaints by net citizens regarding incidents in the city of palembang. The result showed a government official who actively uses social media uses the @plembang.update account as a place to get information to be followed up as part of his work. This shows that the use of social media can be a platform for the government to connect with the community quickly and help with the efficiency of this work.